Electrospun polyacrylonitrile/magnetic Fe3O4–polyhedral oligomeric silsesquioxanes nanocomposite fibers with enhanced filter performance for electrets filter media. Issue 17 (26th July 2016) - Song, Xiaoyan; Cheng, Guoqing; Cheng, Bowen; Xing, Jinfeng
Abstract: Abstract : Magnetic Fe3 O4 –polyhedral oligomeric silsesquioxanes (POSS) particles with Si-OH were prepared by hydrosilylation reaction between the Fe3 O4 –SiH and POSS with hydroxyl and vinyl groups. The magnetic Fe3 O4 –POSS particles were characterized by using transmission electron microscopy, scanning electron microscopy, Fourier transform infrared absorption spectroscopy, thermogravimetry, and vibrating sample magnetometry. The magnetic saturation value of Fe3 O4 –POSS particles was 18.77 emu/g. Polyacrylonitrile (PAN)/Fe3 O4 –POSS nanofibers mats were subsequently fabricated by electrospinning technique. The electret properties of PAN/Fe3 O4 –POSS nanofibers mats and their aerosol filtration property as electrets filter media were characterized. The stability of the surface potential was remarkably improved and the surface potential retention reached 50% for PAN/Fe3 O4 –POSS mats with 1 wt% Fe3 O4 –POSS. Compared with pure PAN, the charge retention of PAN/Fe3 O4 –POSS was increased by 21% and reached 52.40%. Moreover, the collection efficiency increased and the filter resistance decreased when the PAN nanofibers with Fe3 O4 –POSS were used as electrets filter media. Our study provided an effective method to prepare novel filter materials with high efficiency and low resistance.